Uji Kualitatif Kandungan Senyawa Sianida pada Tanaman dengan Metode Pikrat - Khairani, Ayudia Cipta; Ariasti, Mia; Muhsin, Lalu Busyairi; Amrulloh, Lalu Sanik Wahyu Fadil; Martayuni, Ruprika Dwi (Department of Pharmacy, Bumigora University, 2025)
Indonesian people have traditionally utilized various local plants as alternative food sources. These plants are widely available and have considerable nutritional value; however, some of them are known to contain toxic compounds such as cyanide (HCN), which can be harmful to human health if not properly processed. Therefore, this study aimed to examine the presence of cyanide compounds in several of these commonly consumed plants. The research was conducted using a qualitative test based on the picrate method. The samples tested included cassava, cassava leaves, bamboo shoots, gadung tubers, and taro tubers. The findings indicated that all tested samples showed positive results for the presence of cyanide, as evidenced by the observed color change from yellow to reddish-brown. In conclusion, all five types of plant samples tested contained cyanide, emphasizing the importance of proper processing techniques to reduce toxicity levels before consumption by the public.